Characteristics of supernumerary teeth among nonsyndromic dental patients - Szu-Ting Chou; Hong-Po Chang; Yi-Hsin Yang; Chih-Yin Lung; Yu-Chuan Tseng; Chin-Yun Pan; Jung-Husan Cheng (Elsevier, 2015)
Background/purpose: A literature review reveals limited data for supernumerary teeth in Taiwan. Therefore, this study aimed to analyze the characteristics of nonsyndrome associated supernumerary teeth in a Taiwan population. Materials and methods: A retrospective study analyzed 6423 nonsyndromic patients (3300 males and 3123 females; age range: from 4 years, 7 months to 76 years, mean age: 25.03 ± 16.32 years). Diagnosis of supernumerary teeth was based on panoramic radiographic examination. Chi-square test, Chi-square test for trend, and multiple logistic regression analysis were used for statistical analysis. Results: The prevalence rate was 2.6% (248 supernumerary teeth in 167 patients), with a male predominance (1.69:1; P < 0.001). Most supernumerary teeth were single (67.66%), conical (47.98%), and unerupted (79.84%). Supernumerary teeth also tended to be located in the premaxilla (52.82%), fully developed (54.44%), normally oriented (59.27%), sagittally placed in a palatal/lingual position (76.96%), and adjacent to the root and root apex of permanent teeth (63.71%). Conclusion: The prevalence of supernumerary teeth in this study was 2.6%, the most frequent location being at the anterior maxilla. Numerous factors should be considered when evaluating supernumerary teeth. Specifically, the demographic profiles of patients with supernumerary teeth provide useful epidemiological information.